INSTITUTIONAL AND LEGAL MECHANISMS FOR THE PROTECTION OF ENDANGERED SPECIES: THE US EXPERIENCE AND PROSPECTS FOR IMPLEMENTATION INTO THE LEGISLATION OF THE REPUBLIC OF UZBEKISTAN (European Journal of Interdisciplinary Research and Development, 2026)
This article examines the institutional and legal frameworks for protecting endangered species, focusing on modernizing the legislation of the Republic of Uzbekistan through a comparative analysis with the United States’ experience. The author identifies a fundamental problem in domestic law enforcement: the predominance of declarative biological statements over strict administrative-legal procedures. Drawing on the US Endangered Species Act (ESA), the study proposes transitioning from "biologized" categories to differentiated legal regimes and rule-making listing processes. Key recommendations include implementing the "critical habitat" concept to provide flexible spatial protection outside traditional reserves and legalizing digital monitoring tools—such as GIS, UAVs, and remote sensing—as official legal evidence. These reforms aim to balance Uzbekistan's economic development with constitutional environmental guarantees, particularly in ecological disaster zones like the Aral Sea region and Ustyurt Plateau.